Cellular Contractility Profiles of Human Diabetic Corneal Stromal Cells. (7th June 2021) - Lam, Thi N.; Nicholas, Sarah E.; Choi, Alexander; Ma, Jian-Xing; Karamichos, Dimitrios
Abstract : Diabetic keratopathy is a corneal complication of diabetes mellitus (DM). Patients with diabetic keratopathy are prone to developing corneal haze, scarring, recurrent erosions, and significant wound healing defects/delays. The purpose of this study was to determine the contractility profiles in the diabetic human corneal stromal cells and characterize their molecular signatures. Primary human corneal fibroblasts from healthy, Type 1 DM (T1DM), and Type 2 DM (T2DM) donors were cultured using an established 3D collagen gel model. We tracked, measured, and quantified the contractile footprint over 9 days and quantified the modulation of specific corneal/diabetes markers in the conditional media and cell lysates using western blot analysis. Human corneal fibroblasts (HCFs) exhibited delayed and decreased contractility compared to that from T1DMs and T2DMs. Compared to HCFs, T2DMs demonstrated an initial downregulation of collagen I (day 3), followed by a significant upregulation by day 9. Collagen V was significantly upregulated in both T1DMs and T2DMs based on basal secretion, when compared to HCFs. Cell lysates were upregulated in the myofibroblast-associated marker, α -smooth muscle actin, in T2DMs on day 9, corresponding to the significant increase in contractility rate observed at the same time point. Furthermore, our data demonstrated a significant upregulation in IGF-1 expression in T2DMs, when compared to HCFs and T1DMs, at day 9. T1DMs demonstrated significant downregulation of IGF-1 expression, when compared to HCFs. Overall, both T1DMs and T2DMs exhibited increased contractility associated with fibrotic phenotypes. These findings, and future studies, may contribute to better understanding of the pathobiology of diabetic keratopathy and ultimately the development of new therapeutic approaches.